Centrosome aberrations in acute myeloid leukemia are correlated with cytogenetic risk profile - Neben, Kai; Giesecke, Christian; Schweizer, Silja; Ho, Anthony Dick; Krämer, Alwin (Blood, 2003)
Genetic instability is a common feature in acute myeloid leukemia (AML). Centrosome aberrations have been described as a possible cause of aneuploidy in many human tumors. To investigate whether centrosome aberrations correlate with cytogenetic findings in AML, we examined a set of 51 AML samples by using a centrosome-specific antibody to pericentrin. All 51 AML samples analyzed displayed numerical and structural centrosome aberrations (36.0% ± 16.6%) as compared with peripheral blood mononuclear cells from 21 healthy volunteers (5.2% ± 2.0%;P< .0001). In comparison to AML samples with normal chromosome count, the extent of numerical and structural centrosome aberrations was higher in samples with numerical chromosome changes (50.5% ± 14.2% versus 34.3% ± 12.2%;P< .0001). When the frequency of centrosome aberrations was analyzed within cytogenetically defined risk groups, we found a correlation of the extent of centrosome abnormalities to all 3 risk groups (P= .0015), defined as favorable (22.5% ± 7.3%), intermediate (35.3% ± 13.1%), and adverse (50.3% ± 15.6%). These results indicate that centrosome defects may contribute to the acquisition of chromosome aberrations and thereby to the prognosis in AML.